A (2+1)-dimensional breaking soliton equation: Solutions and conservation laws. (February 2018) - Yıldırım, Yakup; Yaşar, Emrullah
Highlights: Lie symmetries and reductions of (2+1) dimenisonal breaking soliton model were carried out. Solitary wave and optical soliton solutions were constructed. Conservation laws of the model were obtained by multiplier/homotopy methods. Abstract: In this paper, we consider a (2+1)-dimensional breaking soliton equation which describe the (2+1)-dimensional interaction of the Riemann wave propagating along the y -axis with a long wave along the x -axis. By the Lie group analysis, the Lie point symmetry generators and symmetry reductions were deduced. From the viewpoint of exact solutions, we have performed two distinct methods to the equation for getting some exact solutions. Kudryashov's simplest methods and ansatz method with the assistance of Maple were carried out. The local conservation laws are also constructed by multiplier/homotopy methods. Finally, the graphical simulations of the exact solutions are depicted.